CXCL10 levels in diagnosis and improved hemodynamics in patients with chronic thromboembolic pulmonary hypertension undergoing balloon pulmonary angioplasty. (7th June 2022) - Hong, Cheng; Lu, Jianmin; Chen, Riken; Liu, Haimin; Chen, Haiming; Wu, Xiaofeng; Guo, Wenliang; Huang, Zijie; Liao, Huizhao
Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is a progressive pulmonary vascular disease characterized by pulmonary artery stenosis or obstructions resulting from insufficient thrombus resolution. Chemokine (C‐X‐C motif) ligand 10 (CXCL10) is a chemokine that contributes to the pathogenesis of many autoimmune diseases and cancers. The present study aims to investigate the levels of CXCL10 in patients with CTEPH throughout balloon pulmonary angioplasty (BPA) and its correlation with the improvement of pulmonary hemodynamics. Plasma CXCL10 levels were measured in 38 CTEPH patients with 100 BPA sessions and in 28 healthy controls. Correlations between CXCL10 and pulmonary hemodynamics were investigated. Receiver operating characteristic (ROC) curves were plotted to display the diagnostic value and the predictive ability for perioperative complications of CXCL10 and CXCL10‐related models. Nomograms were plotted to visualize the diagnostic value and the predictive ability for perioperative complications of CXCL10 and CXCL10‐related models. CXCL10 levels are higher in CTEPH patients compared with healthy controls (36.5 [95% confidence interval CI: 25.0–51.1] vs. 14.8 [95% CI: 11.1–30.9], p < 0.0001) and decreased significantly after BPA treatment (36.5 [95% CI: 25.0–51.1] vs. 24.7 [95% CI: 17.2–36.6], p < 0.0005). Preoperative CXCL10 levels positively correlated with mean right atrial pressure ( r = 0.25), systolic pulmonary artery pressure (PAP; r = 0.28), diastolic PAP ( r = 0.33), mean PAP ( r = 0.36), pulmonary vascular resistance ( r = 0.31), and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP; r = 0.46). Furthermore, plasma CXCL10 levels adjusting for age and sex displayed a sensitivity of 86.0% and a specificity of 67.9% for discriminating CTEPH patients from healthy controls. Preoperative CXCL10 levels, in combination with NT‐proBNP, predicted perioperative complications with a sensitivity of 100.0% and a specificity of 46.9% as displayed in ROC analysis. In conclusion, circulating CXCL10 might contribute to the evaluation of disease severity in CTEPH patients and be useful to evaluate the treatment effect of BPA. Future studies are warranted to further study the relationship between pulmonary hemodynamics and circulating CXCL10.